ANALISIS PENDAPATAN PETANI KOPI PETIK MERAH DI DESA AIR RUPIK KECAMATAN BANDING AGUNG KABUPATEN OGAN KOMERING ULU SELATAN - Mahidin, Andri Irawan, Neng Karmila, Anggi Fatmayati, (JASEP, 2024)
Coffee plants are one source of income for farmers in South OKU Regency. This research aims to analyze the income of red pick coffee farmers. The research was conducted in Air Rupik Village, Banding Agung District, South OKU Regency. The research method used in this research is the survey method. The sampling method in this research used the census method with a population of 31 red pick farmers. Based on the research that has been carried out, it is concluded that the total income of red-picked coffee farmers is IDR 44,954,000.00, which is able to cover all production costs of IDR 15,319,600.00. Thus, the income of red picked coffee farmers per hectare per year is IDR 29,634,400.00.